7 мин 12 сек - 5 мин 16 сек = 1 мин 56 сек
1) 7 мин = 420 сек + 12 сек = 432 сек
2) 5 мин = 300 сек + 16 сек = 316 сек
3) 432 сек - 316 сек = 116 сек= 1 мин 56 сек
1 мин 56с.
Пошаговое объяснение:
7 мин 12 с - 5 мин 16 с = (6 мин + 60 с + 12 с) - (5 мин + 16 с) = (6 мин - 5 мин) + (72 с - 16с) = 1 мин 56с.
7 мин 12 сек - 5 мин 16 сек = 1 мин 56 сек
1) 7 мин = 420 сек + 12 сек = 432 сек
2) 5 мин = 300 сек + 16 сек = 316 сек
3) 432 сек - 316 сек = 116 сек= 1 мин 56 сек
1 мин 56с.
Пошаговое объяснение:
7 мин 12 с - 5 мин 16 с = (6 мин + 60 с + 12 с) - (5 мин + 16 с) = (6 мин - 5 мин) + (72 с - 16с) = 1 мин 56с.